The Effectiveness of Disability Picture Storybooks for Children 5-6 Years Old in Inclusive Kindergarten - Jaswandi, Lathiffida Noor; Kurniawati, Farida (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2023)
Efforts to foster acceptance of children with disabilities can be done by providing knowledge about disabilities through picture storybooks. Unfortunately, researchers have not found picture storybooks about disability in Indonesia that are aimed at kindergarten-age children, so this study aims to test the effectiveness of picture storybooks in increasing knowledge about disability in children aged 5-6 years. This research is a quasi-experimental study with mixed methods (quantitative and qualitative). The intervention was carried out by reading two picture story books, each read three times. Participants in this study were 28 non-disabled children aged 5-6 years and attending inclusive kindergartens. The measuring tool used is the achievement test to measure the increase in knowledge from the information provided. Quantitative results found an increase in knowledge about disability in non-disabled children aged 5-6 years. In addition, the qualitative results show that children can identify the characteristics of disabilities in the story content and are able to relate them to information that children already have. The implication is that teachers and parents can use picture storybooks to introduce disabilities to children aged 5-6 years in Inclusive Kindergarten.